2016
DOI: 10.1111/ijfs.13053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silica gel on reduction in gluten during several beer brewing stages

Abstract: Summary Beer is an alcoholic beverage made with barley as a basic raw material, and therefore, it is not suitable for people with coeliac disease. During the brewing process, the elimination of the haze‐active precursor is performed at the stabilisation stage. Some breweries use silica gel (SG) as stabilisation precursor. This work presents the studies conducted to identify the stage where the addition of SG is more convenient in order to reduce gluten, and the effect on the yeast nutritional value due its inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…by use of tannins ] of gluten proteins and peptides and/or clarification steps [e.g. membrane filtration, use of silica gel (in line with the German Beer Purity Law) ] could help to produce gluten‐free malt beers in a reproducible manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…by use of tannins ] of gluten proteins and peptides and/or clarification steps [e.g. membrane filtration, use of silica gel (in line with the German Beer Purity Law) ] could help to produce gluten‐free malt beers in a reproducible manner.…”
Section: Resultsmentioning
confidence: 99%
“…prolyl‐endopeptidase) and beer stabilizers (e.g. tannins, silica gel) could successfully reduce gluten peptide concentrations to below the gluten‐free threshold .…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have demonstrated that a decrease in gluten occurs during the brewing processes. Furthermore, the addition of processing aids commonly used to stabilise beer by removal of haze‐active proteins also aids in reducing the gluten content of beer (Guerdrum & Bamforth, ; Akeroyd et al ., ; Benítez et al ., ). This occurs because the haze‐forming activity of a protein in beer depends greatly on proline‐rich barley hordeins (Hager et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Proline and its high levels in the hordein protein fraction of the barley grain (Deželak, Zarnkow, Becker, & Košir, 2014) is a key player for the gluten toxicity to coeliac patients or to the growing number of more mildly gluten-intolerant people (Benítez et al, 2016;Hager et al, 2014;Sollid, 2002;Uhde et al, 2016). Therefore, its possible assimilation, degradation and further reduction during fermentation and maturation will be very beneficial to the food safety of the finished beers.…”
Section: Discussionmentioning
confidence: 99%
“…In alternative, complex and costly filtration and enzymatic techniques are used, to condition the malts in order to boost processes leading to the precipitation of proteins, during mashing, fermentation and stabilization (Dostálek, Hochel, Méndez, Hernando, & Gabrovská, 2006;Hager et al, 2014). Another alternative technique consists in the use of silica gel (SG) in the fermentation stage of the brewing process to selectively remove proteins without practically affecting both valuable yeast nutrients such as free amino-nitrogen (FAN) and foam-causing proteins, leading to gluten reduction in the subsequent stabilization stage (Benítez, Acquisgrana, Peruchena, Sosa, & Lozano, 2016). Although silica is generally recognized as a safe (GRAS) food additive both in US and Europe, its use adds to cost and process complexity.…”
Section: Introductionmentioning
confidence: 99%